Kirke, opera og stormoske: Retskulturelle overvejelser over monumentalarkitektur - Petersen, Hanne (Politik, 2010)
The article analyses the notions of legal culture and monumental architecture. It is presumed that symbolic monumental architecture can be interpreted as legal cultural representations and thereby illustrate legal cultural changes. It is exemplified by the Opera and the debates on grand-mosques in Copenhagen. The claim of the article is that these buildings, the opera and the grand-mosques, can be understood as the growth of a post-national marked based legal culture in contrast to a post-national religious based legal culture.